Impacto de la implementación del octógono nutricional en la decisión de compra de alimentos en amas de casa de la ciudad de Iquitos, 2020 - Lozano Salazar, Dennis Carlos (2022)
Nutritional labeling is a useful tool for consumers, where they can make informed and healthy choices. The choice, purchase and consumption of food will depend on consumers, on the nutritional information they use on the labels. It will also influence the taste to read the information, the format and the motivation to use the nutritional labeling. This study addresses the impact of the use of the octagon and nutritional labeling on the decision to purchase processed products by housewives in the city of Iquitos. The research was non-experimental, descriptive with a cross section, and the sample consisted of 800 housewives. A questionnaire was applied to nurses on the use of the octagon and labeling as a data collection instrument. The results reveal that puncha has the highest percentage where housewives have heard about the healthy eating law, with 81.0%, but at the same time they comprise the highest percentage in ignorance of the nutritional label (68%). It is also observed that the housewives are “In favor” and “Totally in favor” of the application of the Healthy Eating Law”. Octagons are much easier to understand as they indicate “High Sugar”, “High Sodium”, “High Trans Fat”. Concluding that, the octagons present in the nutritional label of processed products, "Has changed" in a positive way in the decision to purchase them, understanding each other better, and reducing the consumption of these products.